2022
DOI: 10.1016/j.jstrokecerebrovasdis.2021.106275
|View full text |Cite
|
Sign up to set email alerts
|

Managing Post-Stroke Care During the COVID-19 Pandemic at a Tertiary Care Level Hospital in Peru

Abstract: Objectives: To understand the hospital-to-outpatient care transition and how the discharge process of stroke patients is managed; and to identify potential opportunities to improve these processes, while contrasting pre- and during COVID-19 experiences in Peru. Methods: A qualitative study was conducted between February and March 2021 consisting of in-depth interviews of patients with stroke, their caregivers and healthcare personnel regarding stroke care at a national tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These changes compromised also caregivers' ability to provide safe and effective care to their family members, which was also reported in previous studies (Lee et al, 2021;Sutter-Leve et al, 2021;Zafra-Tanaka et al, 2022). It is well documented in the literature that people post-stroke and their informal caregivers value the support of health services, including learning about the condition and how to deal with it over time in order to take informed decisions about their needs (Chen et al, 2021;Lee et al, 2021;Pereira et al, 2020;Pindus et al, 2018;Theadom et al, 2018).…”
Section: Barriers To Physical Activitysupporting
confidence: 74%
“…These changes compromised also caregivers' ability to provide safe and effective care to their family members, which was also reported in previous studies (Lee et al, 2021;Sutter-Leve et al, 2021;Zafra-Tanaka et al, 2022). It is well documented in the literature that people post-stroke and their informal caregivers value the support of health services, including learning about the condition and how to deal with it over time in order to take informed decisions about their needs (Chen et al, 2021;Lee et al, 2021;Pereira et al, 2020;Pindus et al, 2018;Theadom et al, 2018).…”
Section: Barriers To Physical Activitysupporting
confidence: 74%
“…Recent research has indicated that the successful implementation of performance improvement programs and robust stroke care systems can help maintain high-quality care during health emergencies 114 . Additionally, mitigating delays and preventing reluctance to seek medical care requires addressing various factors such as overcoming fear of COVID-19 infection 115 ; managing transportation restrictions (i.e., many individuals indicated being ensure whether travel to hospital was permitted and feared exposing patients to COVID-19 116 ), and alleviating burdens on the healthcare system. Notably, innovations have been proposed to alleviate these burdens and safeguard stroke survivors during crises, including: (1) implementing teleneurology networks to enhance thrombolysis access for acute ischemic stroke; (2) enhancing the efficiency of emergency care for acute ischemic stroke (e.g., by preregistering patients during transport via ambulance and having the neurologist obtain clinical history electronically prior to arrival at the hospital); and (3) offering alternatives to inpatient care for transient ischemic attacks through an accelerated diagnostic protocol in the observation unit 117 .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis will draw upon data from both the health system assessment and patient journey interviews. Lastly, following the example of a study on post-stroke care management [37], based on the patient journey interviews, a patient journey map will be developed to visualize the experience of PWD, carers and healthcare workers within the healthcare system. The interview data will be organized into pre-designed and newly identified codes using a matrix in Microsoft Excel, after which key milestones will be identified as significant in the patient's experience, as well as those identified by their carers and healthcare workers.…”
Section: Analysis Proceduresmentioning
confidence: 99%